INTRAPLATE VOLCANISM IN NEW ZEALAND: THE ROLE OF FOSSIL PLUME MATERIAL AND VARIABLE LITHOSPHERIC PROPERTIES - Sprung P.; Schuth S.; Münker C.; Hoke L. (My University, 2007)
The geologic evolution of the New Zealand microcontinent was characterised by intermittent Cretaceous to Quaternary episodes of intraplate volcanism. To evaluate the corresponding mantle evolution beneath New Zealand with a specific focus on the tectonic evolution, we performed a combined major and trace element and Hf, Nd, Pb, Sr isotope investigation on a suite of representative intraplate volcanic rocks from both main islands and the Chatham Islands. Isotopically, the data set covers a range between "HIMU-like" end member compositions (206Pb/204Pb: 20.57, 207Pb/ 204Pb: 15.77, 87Sr/86Sr: 0.7030, εHf: + 3.8, εNd: + 4.2), compositions tending towards MORB (206Pb/204Pb: 19.01, 207 Pb/204Pb: 15.62, 87Sr/86Sr: 0.7028, εHf: + 9.9, εNd: + 7.0) and compositions reflecting the influence of subducted sediments (206Pb/204Pb: 18.99, 207Pb/204Pb: 15.67, 87Sr/ 86Sr: 0.7037, εHf: + 4.4, εNd: + 3.9). Whereas volcanism on the Chatham Islands constitutes the HIMU end member of our data set, intraplate volcanic rocks from the North Island are dominated by MORB-like compositions with relatively radiogenic 206Pb/ 204Pb signatures. Volcanic rocks from the South Island form a trend between the three end members. Assuming a polybaric melting column model, the primary melt compositions reflect variations in the degree of melting, coupled to variable average melting depths. As the three isotope and trace element end members occur throughout the volcanic episodes, the "HIMU-like" and the sediment influenced signatures most likely originate from a heterogeneous subcontinental lithospheric mantle, whereas an asthenospheric origin is inferred for the MORB-like component. For the South Island, affinities to HIMU wane with decreasing average melting depths whereas MORB and sediment-like signatures become more distinct. We therefore propose a polybaric melting model involving upper asthenospheric mantle and a lithospheric mantle source that has been modified by subduction components and veins of fossil "HIMU-like" asthenospheric melts. The proportion of asthenospheric versus lithospheric source components is controlled by variations in lithospheric thickness and heat flow, reflecting the different tectonic settings and rates of extension. Generally, low degree melts preferentially tap enriched vein material with HIMU signatures. The widespread occurrence of old Gondwana-derived lithospheric mantle beneath intraplate volcanic fields in East Gondwana is suggested by overall similarities between New Zealand intraplate volcanic rocks and volcanic rocks in East Australia and Antarctica. The petrogenetic model proposed here may therefore serve as a general model for the petrogenesis of Cretaceous to Recent intraplate volcanic rocks in former East Gondwana. © Springer-Verlag 2007.
Keywords: Quaternary; Cretaceous; Cenozoic::Quaternary; Кайнозой::Четвертичная; Mesozoic::Cretaceous; Мезозой::Меловая